Behind Sample Rejection of Nurse’s Role - Duaa Fahad Alkhleef; Khadija Ameen Alkhalifa; Zahra Abdulghani Akhdar; Ibraheem Ahmed Alsaleem; Zainab Saleh Al Ayesh; Shaima Abdullah Alhabib; Haleema Saleh Alhazzom; Suaad Ali Abdullah Al Bakal; Zainab Ahmed Al-Hassan; Amal Hassan Abuallatifah; Nabil Shabib Alshabib; Ali Yaseen J Alkhalaf; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
Sample rejection in the clinical laboratory can lead to delays in diagnosis, increased healthcare costs, and compromised patient care. Nurses play a crucial role in ensuring that samples collected from inpatients meet the required criteria for analysis. This review examines the role of nurses in sample collection, focusing on the importance of adhering to good sample criteria to prevent sample rejection in the clinical laboratory.